The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s42452-019-1820-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of multi-stage manufacturing process of stirling engine crankshaft

Abstract: Crankshafts are among the most important parts in internal combustion engines, of which stirling engine is a useful example. Manufacturing process of a crankshaft, is considered as a three-step forging process using preform, due to the complexity in geometry. The most challenging step of the multistage forging process is to avoid stress concentration and to create uniformity of strain by controlling metal flow. In the present study, the final part was achieved under three manufacturing processes namely: upsett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…A detailed analysis of scientific and technical information on Stirling engines (SE) from a number of foreign countries [1][2][3][4][5] showed that the most important elements in the development of this promising engine are the main heat exchangers of the internal circuit [6][7][8][9][10] and efficient heat supply in the external circuit [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed analysis of scientific and technical information on Stirling engines (SE) from a number of foreign countries [1][2][3][4][5] showed that the most important elements in the development of this promising engine are the main heat exchangers of the internal circuit [6][7][8][9][10] and efficient heat supply in the external circuit [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…time, energy and materials) while maintaining a high accuracy of optimization and/or screening results [28]. Among different techniques of DOE, the Taguchi method, and Response Surface Methodology (RSM) are of the most interest [29,30]. Developing a robust design in which the results are minimally affected by the external noises, is a vital element in DOE for any chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, conducting numerical analysis requires statistical analysis [11][12][13][14][15] and experimental design, susceptible to errors and barriers such as uncertainty [16]. On the other hand, every experimental work needs a good calibration and inspection [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%